Contemporary stroke prevention strategies in 11 096 European patients with atrial fibrillation: a report from the EURObservational Research Programme on Atrial Fibrillation (EORP-AF) Long-Term General Registry - Boriani, Giuseppe; Proietti, Marco; Laroche, Cécile; Fauchier, Laurent; Marin, Francisco; Nabauer, Michael; Potpara, Tatjana; Dan, Gheorghe-Andrei; Kalarus, Zbigniew; Diemberger, Igor; Tavazzi, Luigi; Maggioni, Aldo P; et al. (Oxford University Press (OUP), 2018)
Contemporary data regarding atrial fibrillation (AF) management and current use of oral anticoagulants (OACs) for stroke prevention are needed.